2008
DOI: 10.1080/15389580701775843
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Knowledge and Attitudes About Preventing Injuries in Motor Vehicle Accidents in Children in Greece

Abstract: The adoption of harsh measures for preventing the devastating consequences of car accidents in children is of high importance. Parents' rigorous education must become our priority. Health care professionals need to act dynamically in sensitizing Greek parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Sociodemographic influences, including education and income level have all been associated with booster seat use. It has been commonly reported that parents of lower income and education levels report lower rates of booster seat use in comparison with those of higher socioeconomic status 14 15 18 19…”
Section: Introductionmentioning
confidence: 99%
“…Sociodemographic influences, including education and income level have all been associated with booster seat use. It has been commonly reported that parents of lower income and education levels report lower rates of booster seat use in comparison with those of higher socioeconomic status 14 15 18 19…”
Section: Introductionmentioning
confidence: 99%
“…This finding is aligned with other scientific evidence. The Toumakas et al18 study found that the caregivers with higher level of education were more informed about risk and prevention of injuries in motor vehicle crashes. Toumakas explained these results by indicating that educated parents are more willing to obtain information concerning current issues 18.…”
Section: Discussionmentioning
confidence: 99%
“…The Toumakas et al18 study found that the caregivers with higher level of education were more informed about risk and prevention of injuries in motor vehicle crashes. Toumakas explained these results by indicating that educated parents are more willing to obtain information concerning current issues 18. Education level might also play a role in understanding the complicated directions and process involved in properly installing and using a car seat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations